Parenting Pattern of Associated School Students in Sman Titian Teras H. Abdurrahman Sayoety Jambi - Mulyadi Mulyadi (Green Publisher Indonesia, 2021)
The purpose of this study was to determine the description of parenting patterns, the benefits felt by students, and the supporting and inhibiting factors for the implementation of assimilation at SMAN Titian Teras Jambi Boarding School. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Data analysis techniques in this research are data reduction, data display, conclusion drawing/verification. Checking the validity of the data in this study is the credibility test. The results showed that spiritual development consists of the habadah habit. Academic coaching, namely the existence of a subject clinic service at night, the English Club. Non-academic / skill development includes extracurricular activities, development of talents and interests, and defending the country. The benefits felt by the students were that students were accustomed to being diligent in worshiping, understanding the meaning of the Koran, and memorizing the Koran to increase. Students can live independently and have many friends, the student's academic score increases, students gain skills.